History of Mathematics Education in China - Mustafa, Ade Nandang (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2020)
China has a very long history of contributing to human civilisation, including its contribution to mathematics development. The Chinese had discovered many essential theories and concepts in mathematics long before the more famous Western mathematicians. Many of China's theories and concepts thousands of years ago have become references to many Western mathematicians. This paper traces the development of mathematics in China from all the dynasties in its history, including the development of mathematical theory, mathematical texts, and the famous mathematical figures of his time.